Synthesis and characterization of efficient TiO2 mesoporous photocatalysts - Ovodok, Evgeni (2018)
Mesoporous TiO2 powder with large surface area and high porosity was prepared via template-free method of heat-stimulated oxidizing destruction of TiC by HNO3. Anatase crystalline phase of as-prepared and annealed at 200−400 °C titania was confirmed by XRD technique. Surface nitrate-nitro groups responsible for high adsorption capacity of the TiO2 powders were studied by FTIR spectroscopy. The annealing temperature can be used as a factor for regulation of titania morphology and structural properties. The rise in the annealing temperature higher than the temperature of nitrate-nitro groups decomposition induces the growth of TiO2 crystallites, decreasing porosity and surface area, the drop of adsorption capacity, and improving photocatalytic activity under UV irradiation.